2015
DOI: 10.1007/s11357-015-9822-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional measures, inflammatory markers and endothelin-1 as predictors of 360-day survival in centenarians

Abstract: Centenarians represent a rapidly growing population. To better characterize this specific age group, we have performed a cross-sectional study to observe associations between functional measures and a range of biochemical markers, including inflammatory markers and their significance as predictors of 360-day survival. Medical history and physical and functional assessment (Mini-Mental State Examination (MMSE), Katz Index (activities of daily living, ADL) and Barthel Index (Barthel Index) of Activities of Daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…Findings in this study are consistent with an earlier study which reported that disability in bADLs is a strong predictor of survival amongst centenarians [ 20 ]. A recent study reported an adjusted hazard ratio per disability increment in KI of 1.6 among hospitalised patients aged 83 years and above [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Findings in this study are consistent with an earlier study which reported that disability in bADLs is a strong predictor of survival amongst centenarians [ 20 ]. A recent study reported an adjusted hazard ratio per disability increment in KI of 1.6 among hospitalised patients aged 83 years and above [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several different instruments for evaluating frailty, comorbidity, or disability have been developed. 4 , 5 , 20 , 22 , 23 , 49 51 , 53 It might be misleading to compare our findings with those obtained using other instruments than were applied in the study presented here for assessing frailty, comorbidity, or disability.…”
Section: Discussionmentioning
confidence: 80%
“… 50 ADL disability in the items of the Katz index was at least as powerful in predicting 360-day mortality as ADL disability based on the Barthel index in 86 centenarians (102±1 years old). 51 ADL disability according to the Katz index had the highest impact on mortality during a mean follow-up period of 2.8 years, among other parameters, in 1,099 older Swedish persons with an age of 77–100 years from the Kungsholmen Project. 42 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Physical activity has protective effects on ageing and data have shown that high levels of house work and recreational activity are independently associated with lower CRP levels in the elderly . In an observational study of 360‐day survival in centenarians, higher CRP level was found to be inversely associated with lower survival time . In a 10‐year follow‐up of the Framingham Offspring Study including 934 participants aged ≥60 years, McCabe et al.…”
Section: Crp and Healthy (Successful) Ageingmentioning
confidence: 99%